Safety knowledge-attitude-behaviour KAB among manufacturing workers in Malaysia: a proposed research of designing and developing an intervention module - Zulkifly, Syazwan Syah; Hasan, Nor Halim; Baharudin, Mohd Rafee; Syed Ismail, Sharifah Norkhadijah; Mahadi, Muhammad Razif (AiBMA, 2021)
Workplace accident has become a prominent issue in Malaysia this decade with the number of reported accident cases have recently shown a gradual upturn. Safety behaviour is found to be the leading cause of workplace accident, and previous researchers have found that safety knowledge and safety attitude are among the significant predictors of safety behaviour. Therefore, this paper proposes a design and development research (DDR) to produce a valid, reliable, and tested intervention module fostering safety behaviour through improving workplace safety knowledge, and also safety attitude of manufacturing workers. In terms of methodology, a DDR needs to undergo three phases, namely Phase 1 (analysis of need), Phase 2 (module design & develop), and Phase 3 (usability evaluation). In Phase 1, this paper proposes a cross-sectional study using a questionnaire to determine the relationship between safety “KAB”. For Phase 2, the Nominal Group Technique (NGT) is proposed for the process of content validity. Lastly in Phase 3, a quasi-experimental design with a control group is suggested in evaluating the effectiveness of the module. This research proposal will provide an initial reference for researchers to conduct applied research for workplace accident’s solution. Besides, it could also initiate the relevant authority agencies as well as the management of manufacturing companies to design and develop a valid and reliable module for workplace safety intervention.